(untitled) (European Journal of Health Research, 2021)
Nursing is exposed to a variety of occupational stress affecting their psychological health and productivity. Psychological flexibility has been shown to have beneficial effects on mental health of general population. The aims of this study were to analyze in nursing staff the relationship between the exposure to work-related stressors and psychological flexibility; and between emotional symptomatology and psychological flexibility; and the differences of the exposure to work-related stressors and emotional symptomatology among different work areas and different shift work. A correlational-comparative study has been developed. In addition to sociodemographic and work variables, the NSS, DASS-21, AAQ-II questionnaires were used to measure the work-related stressors, stress, anxiety, depression, and psychological flexibility, respectively. The prevalence of moderate-very severe levels of depression, anxiety and stress was 17.6%, 29.9% and 23.3%, respectively. A significant negative correlation was observed between work-related stressors and psychological flexibility; between occupational stress and psychological flexibility; between emotional symptomatology and psychological flexibility; between anxiety, stress and age; between work-related stressors and age. Nurses working rotating shifts reported significantly higher levels of emotional symptomatology, stress and anxiety than those working day shifts. Psychological flexibility seems to explain a significant prevalence of emotional symptomatology in nurses. Community nurses showed the lowest levels of anxiety, depression and stress when compared to hospital nurses working in different areas.